A Study of Family Process Factors of Social Anxiety on the Internet Based on Big Data—Take Guangxi University Students as an Example - Bi, Dexu (Frontiers in Public Health, 2022)
Background Along with the popularization of the new medium of interpersonal communication, many researchers have found that the use of social media has brought about many mental health problems. For example, the virtual nature, vulnerability, and uncertainty of online communication lead to reduced online trust, causing interaction anxiety (IA). The data footprints left on the Internet are processed by malicious elements for big data, leading to the leakage of personal privacy data, bringing content sharing anxiety (SAC) and privacy concern anxiety (PAC), which are all typical forms of online social anxiety. In the face of this situation, analyzing the influence of online social networking on the social psychology of university students and guiding it has become an inevitable issue in the Internet era. Methods Learning from the classification of family environment, a self-administered family process factor questionnaire and the Social Anxiety Scale for Social Media Users (SAS-SMU) were used to investigate the online social anxiety of Guangxi University students. The study used SPSS26.0 and Stata for data analysis and descriptive statistics, ANOVA, t-test, and linear regression analysis were used to explore the relationship between family process factors and online social anxiety of the university students. Results The results showed that except for parental supervision (p > 0.05), the effects of interparental relationship, parent-child relationship, sibling relationship, and family atmosphere on university students' online social anxiety were statistically significant and showed positive correlations (F/t = 6.64, 3.53, 4.15, 5.94; p < 0.05). Multiple linear regression analysis showed that university students' total online social anxiety score = 36.914−4.09 × good parental relationship−4.16 × good family atmosphere−3.42 × good sibling relationship. Conclusions Based on the family systems theory, it is suggested that a comprehensive intervention should be conducted for the coupled system (parental relationship) and sibling system (non-only child's sibling relationship) in the family and focus on the protective factors of parental harmony, sibling relationship harmony, and relaxed family atmosphere. In the specific implementation method, the collaborative shared healthcare plan (CSHCP) can be used to strengthen remote family emotional interaction and avoid Internet addiction. For university students with online social anxiety disorders, their personal health records (PHRs) can be maintained permanently and safely using the Star File System (IPFS), in addition to the convenience of IPFS data extraction, which is more conducive to the timely and long-term tracking treatment of anxious university students.